DHEA Administration Activates Transcription of Muscular Lipid Metabolic Enzymes via PPARα and PPARδ in Obese Rats - Horii, N.; Sato, K.; Mesaki, N.; Iemitsu, M. (Hormone and Metabolic Research, 2016)
Administration of dehydroepiandrosterone (DHEA), a precursor of sex steroid hormones, reduces total and visceral fat mass and elevates adipocytic adiponectin gene expression. The aim of this study is to investigate whether levels of peroxisome proliferator-activated receptors (PPARs) in muscle and transcription of PPAR target genes are affected by long-term DHEA administration or exercise training, and whether altered PPAR levels are associated with circulating adiponectin level in obese rats. After 14 weeks on a high-sucrose diet, obese male Wistar rats were assigned randomly to one of 3 groups: control, DHEA administration (1 mg/kg body weight), or exercise training (treadmill running for 1 h, 25 m/min, 5 days/week) for 6 weeks (n=7 for each group). Plasma DHEA and total adiponectin levels in the DHEA-treated and exercise-training groups were significantly higher than those in the obese control group. Additionally, DHEA administration and exercise training significantly increased muscular PPARα and PPARδ protein levels, with a concomitant increase in mRNA expression of 3β-hydroxyacyl-CoA dehydrogenase and cytochrome c oxidase IV, which are target genes of PPARα and PPARδ respectively. Moreover, DHEA administration increased these protein and mRNA levels to the same degree as exercise training. Circulating adiponectin level was positively correlated with plasma DHEA and with muscle levels of PPARα and PPARδ. These results suggest that in obese rats, secretion of adiponectin due to chronic DHEA administration and exercise training may contribute to an increase in the transcription of genes encoding lipid metabolic enzymes, mediated via elevated expression of PPARα and PPARδ in muscle.
Keywords: dehydroepiandrosterone; skeletal muscle; peroxisome proliferator-activated receptor